Learning object model recognition based on theoretical grounds - Yazrina , Yazrina; Mohammed, Yusoff

(untitled)
Learning object (LO) is a reusable unit of instruction for teaching typically in e-learning environment or any entity, digital, non digital which can be used, reused or referenced during technology supported learning. The idea of LO has already emerged as early as in the nineties, where the concept was then concerned about storing digital learning material into the database. However due to the exponential growth of the World Wide Web, this concept re-emerges and are presently being further developed to generate knowledge and insight in online storing and retrieving LO. Nevertheless, despite being an educational agenda and numerous works performed by researchers related to LO, these researches are less than satisfying. There remains a vacuum in identifying the structure of LO, the pedagogical elements in LO metadata and enhancement of reusability features of LO. In addition there is also problem in obtaining the solid definition of LO despite several attempts made to identify the definition and view of LO. These attempts mainly derived definitions that are broad in meaning and have not defined a complete definition backed with well founded theoretical knowledge. As such it is desirable, to achieve and produce a comprehensive definition of LO based on theoretical knowledge and utilised the definition to procure the LO conceptual structure or model and its types. Therefore this paper will address the development of LO model and its components based on theoretical grounds. In addition, a working prototype system (MELOR) is also described as a proof-of-concept to demonstrate the credibility of the LO model obtained. The model derived is belief to be of use as a guideline to provide a better aspect of what a learning object is and enhance LO reusability features and pedagogical aspects. As such it would lead to greater usage of LO in the future and provide the basis for LO related matters proliferation. (Authors' abstract)